Inhibition of NO-synthase and degranulation of rat omental mast cells in vitro - A. M. Northover; B. J. Northover (Mediators of Inflammation)
Mast cell amines, platelet-activating factor (PAF), thromboxanes and leukotrienes have been shown to be released during nitric oxide-synthase inhibition in the rat intestine. Mast cells in rat isolated omentum (OMCs) or isolated from the rat peritoneal cavity (PMCs) have been used here to investigate the relationship(s) between these agents. N-nitro-L-arginine methyl ester (L-NAME, 100 μM) caused some degranulation of OMCs, but no enhancement of histamine release from PMCs. PAF (5 μM) and U46619 (1 μM) degranulated OMCs and enhanced histamine release from PMCs. Pre-treatment of the omentum with BN52021 (10 μM) inhibited degranulation of OMCs in response to L-NAME, PAF or U46619. Pretreatment with 1-benzylimidazole (5 or 50 μM) inhibited the effect of L-NAME but not that of PAF. Indomethacin (1 μM) or sodium nitroprusside (10 μM) also inhibited the effects of L-NAME, but nordihydroguaiaretic acid (30 μM) did not. In PMCs BN52021 inhibited PAF-induced, but not U46619-induced, release of histamine. These results suggest that inhibition of nitric oxidesynthase in the omentum by L-NAME allows thromboxanes to release PAF, which in turn degranulates and releases histamine from OMCs.